(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: The African giant rat, AGR, is known for advantageous behavioural patterns among which are cognition and dexterous locomotion. This study investigated the morphological, morphometric and possible functional aspects of the AGR spinal cord (SC) anatomy. Ten adult (5 males and 5 females) AGR were used to determine the gross and histological features of the SC which were typically of rodent features. The mean SC weight and length given as 2.50±0.24g and 15.87±0.24cm respectively for the male and 2.32±0.16g and 15.40±0.61cm for the female showed no sexual dimorphism (p<.05). A positive linear relationship between the tail length and SC weight were found in both sexes (r =0.81 males; r =0.95 females) suggesting significant contribution of the filum terminale to SC weight. Forty-three internal structures including nuclear aggregations and tracts were traced. Eight nuclear aggregations of neurons involved in nociception and limb coordination were observed to be prominent and larger than in laboratory rats. Same was noted for the dorsal, ventral and lateral funicular tracts which control the limbic system. This study provides morphometric baseline research information and delineates the functional aspects of the AGR SC anatomy. The information provided further strengthens the drive proposing the AGR as an indigenous research model for regional anaesthesia and locomotor disease.